Stunting Prevention Education for Mothers of Toddlers Withresponsive Feeding in Sirnajaya Village Tarogong Kaler District, Garut Regency - Novianti Rizki Amalia; Hilman Mulyana; Maria Ulfah Jamil; Iis Sopiah Suryani; Birry Assidiqy; Asep Rahmadiana; Fitriani Mardiana (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT In Indonesia, stunting is a serious problem and is also a major nutritional problem currently being faced. If this problem is chronic, it will affect cognitive function, namely low intelligence levels and impact the quality of human resources. Counseling was carried out through lectures and leaflet distribution. Evaluation and monitoring were carried out with questionnaires before and after 1 week of counseling. The counseling program was effective in improving mothers' understanding and behavior towards responsive feeding for toddlers. The level of understanding increased by 94.03% after counseling, indicating a change in mothers' behavior towards their toddlers of 80.45% towards responsive feeding. This Community Service was carried out on August 19-29, 2025 in Di Village, Sirnajaya,Tarogong Kaler District, Garut Regency. The target of this Community Service is mothers who have toddlers. Keywords: Stunting, Mother, Toddler, Responsive Feeding, Education.